Effect of treatment willingness on specialist assessment and treatment uptake for hepatitis C virus infection among people who use drugs: the ETHOS study. Issue 11 (21st May 2015) - Alavi, M.; Micallef, M.; Fortier, E.; Dunlop, A. J.; Balcomb, A. C.; Day, C. A.; Treloar, C.; Bath, N.; Haber, P. S.; Dore, G. J.; Grebely, J.; the ETHOS Study Group
Summary Among people who inject drugs (PWID) with chronic HCV, the association between HCV treatment willingness and intent, and HCV specialist assessment and treatment were evaluated. The Enhancing Treatment for Hepatitis C in Opioid Substitution Settings (ETHOS) is a prospective observational cohort. Recruitment was through six opioid substitution treatment clinics, two community health centres and one Aboriginal community controlled health organisation in Australia. Analyses were performed using logistic regression. Among 415 participants (mean age 41 years, 71% male), 67% were 'definitely willing' to receive HCV treatment and 70% reported plans to initiate therapy 12 months postenrolment. Those definitely willing to receive HCV treatment were more likely to undergo specialist assessment (64% vs 32%, P < 0.001) and initiate therapy (36% vs 9%, P < 0.001), compared to those with lower treatment willingness. Those with early HCV treatment plans were more likely to undergo specialist assessment (65% vs 27%, P < 0.001) and initiate therapy (36% vs 5%, P < 0.001), compared to those without early plans. In adjusted analyses, HCV treatment willingness independently predicted specialist assessment (aOR 3.06, 95% CI 1.90, 4.94) and treatment uptake (aOR 4.33, 95% CI 2.14, 8.76). In adjusted analysis, having early HCV treatment plans independently predicted specialist assessment (aOR 4.38, 95% CI 2.63, 7.29) and treatment uptake (aOR 9.79, 95% CI 3.70, 25.93). HCV treatment willingness was high and predicted specialist assessment and treatment. Strategies for enhanced HCV care should be developed with an initial focus on people willing to receive treatment and to increase treatment willingness among those less willing.